FACTORS INFLUENCING THE FORMATION OF CONGENITAL SPINAL HERNIAS COMBINED WITH BRAIN MALFORMATIONS - Gaybiyev Akmal Ahmadjonovich; Fayzimurodov Fahriddin Tolipovich; Natalya Fedorovna Vyazikova (Scholar Express Journals, 2024)
Modern neonatology in the last decade is faced with a special problem: congenital anomalies of the spine in newborn children, the main mechanism of which is the absence (more often at the level of the lumbosacral region) of one or more vertebrae, thus forming a defect of bone tissues, with subsequent formation of a spinal canal, then the canal pushes into the void of the formed bone defect, and models a congenital spinal hernia, which experts designate as spina bifida or meningoceles.
Keywords: etiologic factors; clinical and instrumental signs; congenital spinal hernias